Review of the indoor environmental quality and energy consumption studies for low income households in Europe - Kolokotsa, D.; Santamouris, M. (The Science of the total environment, 2015)
The term energy poverty is used to describe a situation of a household not able to satisfy socially and materially the required levels of its energy services. Energy and fuel poverty is an increasing problem in the European Union. Although the specific conditions vary from country to country the drivers defining fuel and energy poverty are similar in all Europe. This paper aims to present the state of the art regarding the energy demand and indoor environmental quality of low income households in Europe. The characteristics of this specific population group are presented including details on the specific energy consumption, the indoor comfort and finally the impact of the specific living conditions on the occupants' health. [Display omitted] •The energy and indoor environmental problems for low-income population are analysed.•Low cost heating equipment creates a critical environmental burden during winter.•Discomfort and heat stress is recorded during summer.•Common indices and criteria should be adopted at European level.